COVID-19 Fear and COVID-19 Anxiety as Predictors of Exercise Benefit-Barrier Perception in Type 2 Diabetes Patients in the COVID-19 process : Exercise Benefit-Barrier Perception in Type 2 Diabetes Patients - Arda Sürücü, Hamdiye; sungur, Meltem; Temiz, Ezgi Nur (Health & Research Journal, 2024)
Background: Exercise is an important building block in the management of type 2 diabetes. Perceptions of benefits and barriers related to that behavior may affect individuals' tendency towards protective behaviors such as exercise. Aim: The aim of this study was to examine the fear of COVID-19, anxiety of COVID-19 and descriptive features as predictors of exercise benefit-barrier perception in type 2 diabetes patients during the COVID-19. Method: The research sample consisted of 161 patients with type 2 diabetes. Patient diagnosis form, Exercise Benefits-Barriers Scale, Coronavirus (COVID-19) Fear Scale (CFS) and Coronavirus Anxiety Scale (CAS) were used as data collection tools. The data was shown as percentage and mean ± standard deviation (SD), and Pearson/Spearmen correlation and linear regression analyses were used to examine the relationship between the variables. Results: In the study, when asked what the biggest barrier to exercising as a person with diabetes was, 38.31% of the individuals with type 2 diabetes said "COVID-19 pandemic". The total exercise benefit perception of individuals with diabetes was significant (F: 17.873, p<.001). In addition, for the perception of total exercise benefit, paying attention to risky situations (Hypoglycemia or hyperglycemia preventive behaviors) before doing physical activity (β = -.384), development of diabetic foot in the last six months (β =.163), COVID-19 anxiety (β =.205) were found to be statistically significant predictors (p<.001). Conclusion: At the end of the study, it was found that illiteracy, having a history of diabetic foot development in the last six months, being married and an increase in the level of COVID-19 anxiety increased the perception of exercise benefit in individuals with Type 2 diabetes.